Microstructural, electrochemical, and hot corrosion analysis of CoCrFeCuTi high entropy alloy reinforced titanium matrix composites synthesized by microwave sintering - S. Ragunath; N. Radhika; S Aravind Krishna; Alokesh Pramanik (International Journal of Lightweight Materials and Manufacture)
CoCrFeCuTi High Entropy Alloy (HEA) is reinforced in Ti6Al6V2Sn alloy through microwave sintering-assisted powder metallurgy and its corrosion behaviour is investigated under different conditions. The ball-milled CoCrFeCuTi HEA powder exhibits 17 μm average particle size of irregular fragments with a single-phase BCC structure and is added as reinforcement in Ti alloy at 3, 6, 9, and 12 wt%. As more reinforcement is added, the α-Ti decreases and β-Ti increases which enhances the interfacial bonding. The pinning effects from reinforcements inhibit grain growth contributing to improved properties including higher relative density with less porosity. The 12 wt% composite showed remarkable microhardness of 734 HV which is increased by 43.8% over Ti alloy. The 12 wt% composite also achieved finer grains (0.345 μm) due to uniform internal heat generation from the process. Corrosion behaviour is assessed through electrochemical corrosion and hot corrosion analysis, with 12 wt% composite demonstrating better corrosion resistance compared to Ti alloy. The induced corrosion products, formation of passivation films, and their mechanism are examined by morphological analysis.